The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1186/s12873-015-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute toluene intoxication–clinical presentation, management and prognosis: a prospective observational study

Abstract: BackgroundToluene is one of the most widely abused inhaled drugs due to its acute neurologic effects including euphoria and subsequent depression. However, dangerous metabolic abnormalities are associated to acute toluene intoxication. It has been previously reported that rhabdomyolysis and acute hepatorenal injury could be hallmarks of the condition, and could constitute risk factors for poor outcomes. The objective was to describe the clinical presentation, to characterize the renal and liver abnormalities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 37 publications
0
30
0
8
Order By: Relevance
“…Differently, it was reported that ALP was not elevated and GGT was only mildly elevated in patients who died. 12 In our patient although ALP and GGT levels were normal; both jaundice, which is a sign of hepatobiliary injury, and elevated transaminases were the evidences of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…Differently, it was reported that ALP was not elevated and GGT was only mildly elevated in patients who died. 12 In our patient although ALP and GGT levels were normal; both jaundice, which is a sign of hepatobiliary injury, and elevated transaminases were the evidences of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 40%
“…11 Previous reports showed that acute inhalation produces a biphasic response with an initial CNS excitation followed by CNS depression. 11,12 We believe that the first stage, in our case which is thought to be euphoria, happened before admission.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Resolution of symptoms is often rapid. Nevertheless, toluene abuse is neither harmless nor an insignificant consideration—mortality of 15% was reported in a recent study 12. Toluene abuse is an important, yet often missed, differential diagnosis for the patient with weakness, abdominal complaints and metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, considering the use of BTEX in several industrial segments, its difficulty in dispersing in these environments, its toxic potential and the permanence of the worker for extended periods of time in the work place [11], [12], it is important to monitor these compounds in the occupational environment. Although there are previous reports on the toxicity of the BTEX constituents [13]- [15], there is little information about the toxicity of BTEX as a group.…”
Section: Introductionmentioning
confidence: 99%